The Frankfurt School: A Study in the Thought of Horkheimer and Habermas - Al-Alawi, Nahawand (Al-Adab Journal, 2024)
Critical theory developed by the pioneers of the Frankfurt School dates back to 1923 when the Institute for Social Research was founded in Frankfurt after World War I. The founders and members of the Institute sought to know and understand social life, and to reveal the contradiction between the abundance of resources and the enormous scale of misery and misery, between technological capabilities and the widespread exploitation and destruction, between the supposed freedom of man and the prevailing authoritarian tendency, between free exchange and social injustice, between the free economy and monopoly, and between the world of Man and the world of capital, between the independence of art and its commodification and objectification, and between the supposed enlightenment and emancipatory role of the culture industry and its falsification of consciousness and suppression of difference. Thus, the members of the school were interested in the theoretical framing of new forms of state monopoly capitalism, cultural industry, authoritarian personality, and patterns of oppressive social control, within the framework of social criticism that aims for comprehensive, radical change.